2008
DOI: 10.1007/s00128-008-9416-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Some Soil Parameters on Heavy Metals Accumulation by Vegetables Grown in Agricultural Soils of Different Soil Orders

Abstract: The main purpose of this research was to determine the levels of heavy metals in tomato, potato and lettuce, grown in agricultural soils of different soil orders (Alfisols, Endisols and Vertisols), located at Central Greece. Soil samples were analysed for available forms (after extraction with DTPA) and for total concentrations (after digestion with Aqua Regia) of metals. Zn, Cu, Cr and Ni were the common metals detected in the vegetables studied. Pb and Cd concentrations were low and in some cases not detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 20 publications
5
35
0
2
Order By: Relevance
“…A lower mobility and/or plantavailability of lead compared to other elements such as Cd and Zn was confirmed in this experiment as well as by Huang et al [35] and Sawidis et al [36]. The lead content in lettuce was variable by location and affected by individual soil physicochemical conditions, especially pH levels and clay content in the soils [12]. In our case, lead uptake by plants was influenced by soil type and was affected predominantly by differing mobile content of lead.…”
Section: Leadsupporting
confidence: 88%
See 1 more Smart Citation
“…A lower mobility and/or plantavailability of lead compared to other elements such as Cd and Zn was confirmed in this experiment as well as by Huang et al [35] and Sawidis et al [36]. The lead content in lettuce was variable by location and affected by individual soil physicochemical conditions, especially pH levels and clay content in the soils [12]. In our case, lead uptake by plants was influenced by soil type and was affected predominantly by differing mobile content of lead.…”
Section: Leadsupporting
confidence: 88%
“…In our case, lead uptake by plants was influenced by soil type and was affected predominantly by differing mobile content of lead. Golia et al [12] determined Pb levels in the range from 0.01 to 0.12 mg kg -1 dry matter in lettuce leaves growing in uncontaminated areas, Kabata-Pendias and Pendias [10] reported a concentration range between 0.7 and 3.6 mg kg -1 dry matter. Also, Bagdatlioglu et al [30] determined low levels of Pb in lettuce (1.63±0.70 mg kg -1 ) and chard (1.06±0.67 mg kg -1 ) if ca.…”
Section: Leadmentioning
confidence: 99%
“…On the other hand, cereals do also contain heavy metals which, on the contrary, are not essential for the organism, and penetrate through the ground, the air and the water [14]. The importance of these routes of penetration depends on the type of ground and where it is placed and the agricultural practices that have been used.…”
Section: E D Doe Et Al: Levels Of Selected Heavy Metals In Wheat Fmentioning
confidence: 99%
“…Studies by Golia et al (2008) have shown that low soil pH may induce metals to be soluble and have ion exchange comparable to high soil pH. Studies by (Shivhare and Sharma 2012) demonstrated that the pH of soil affects the solubility and mobility of Ni and other heavy metals.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…CEC and clay content greatly influence the distribution of heavy metals in soils. The pH value and the percentage of clay content determine the solubility of metals in the soil and their availability for uptake by plants (Golia et al 2008). Heavy metals content usually decreases from clay to coarse silt due to relatively high surface area of clay minerals and weak pH dependence of CEC (Modaihsh et al 2004).…”
Section: Profile Distributionmentioning
confidence: 99%